INTEGRATING SOFT SKILLS INTO A TEACHER EDUCATION CURRICULUM - STEPHEN MAREN, MACQUAL; SALLEH, UMI KALSUM MOHD.; ZULNAIDI, HUTKEMRI (International Journal of Psychosocial Rehabilitation, 2024)
Recent developments suggest that soon, soft skillsare likely to become moreimportant insustaining teachers duringteaching. This study looks at pre-service teachers’ soft skillsgained from participation insoft skillscourses that are compulsory second- and third-yearundergraduate teacher education course designed to equip preservice teachers withsustainablesoft skills.We grounded our study on acceptance and commitment training, andsocial change modelto examine the extent soft skills can be effectively fostered in teachereducation.We used paper questionnaires and performed data analysis usingSPSS andSmartPLS software in aquasi-experimental procedure with a population of 722 pre-serviceteachers.In all semesters scores on the soft skills scales showed significant improvement overthe course of the semester, with moderate to large positive effect. Experienced and novicepre-service teachers were compared. Importantly, it was found that the effect of the coursefostering was successful across participants as analysis did not show any significantdifference between the participants in the soft skills self-rated scales. Partial least squarestructural equation modelling analysis revealed interestinglythat all the pre-service teachersgained soft skills in levels that were both moderate and significant.Implying the strength ofthe soft skills curriculum and the credit-hours allocated must be examined.